A facile Ion-Exchange assisted chemical bath deposition of CuSbS2 for thin film solar cells. (15th September 2022) - Lin, Wen-Wei; Wang, Ning-Wei; Lan, Ze-Ying; Huang, Zhi-Ping; Lin, Li-Mei; Ye, Qing-Ying; Chen, Shui-Yuan; Chen, Gui-Lin
Graphical abstract: A facile ion-exchange assisted chemical bath deposition of CuSbS2 for thin film solar cells and exploration of chemical bath mechanism, which achieved the champion efficiency in chemical bath deposition of CuSbS2 solar cells and enriched the environmentally friendly inorganic solar cell preparation process. Highlights: A facile ion-exchange assisted chemical bath deposition is firstly explored for CuSbS2 compound. Pure phase CuSbS2 thin films with uniform and crystalline were prepared. Achieved a champion efficiency of 0.75% for CBD-based CuSbS2 solar cells. Abstract: Copper antimony sulfur (CuSbS2 ) possesses a band gap of about 1.5 eV, high absorption coefficient of > 10 4 cm −1 and abundant compositions, which is considered as one of the potential photovoltaic absorbers. In this work, we propose a facile ion-exchange assisted chemical bath deposition (IEACBD) method, which uses Cu + to replace Sb 3+ from the matrix of Sb2 S3 and then combine into CuSbS2 alloy. Through systematic study, we found that this ion-exchange is a simultaneous interdiffusion process of Cu + and Sb 3+ ions, which enables a uniform mixture of those two elements. But it also inevitably produces a Sb2 O3 by-product on the surface of the film because of the alkaline environment of this chemical bath. To further remove it, we introduce a mild etching process with BDCA solution for Sb2 O3 and then obtain a high-quality CuSbS2 . Finally, we assemble an inorganic CuSbS2 solar cell with the architecture of FTO/TiO2 /CdS/CuSbS2 /Carbon/Ag, and delivering a photoelectric conversion efficiency of 0.75 %. This enriches the preparation method of CuSbS2 thin film and also provides guidance for the synthesis of the similar multiple chalcogen compounds.